Fraud Hexagon and Dark Personality Traits in Academic Dishonesty: Evidence from Indonesian Accounting Students - Arum Prastiwi; Sari Atmini; Hisky Ryan Kawulur (Jurnal Ilmiah Akuntansi, 2025)
This study examines the factors that influence academic fraud behavior among accounting students in Indonesia using the Fraud Hexagon theory, while also testing the moderating role of Dark Triad personality traits. Academic fraud remains a persistent issue in higher education, often exacerbated by psychological, systemic, and contextual factors. Using a quantitative survey approach, data were collected from 220 accounting students at various Indonesian universities through convenience sampling. The variables measured included six dimensions of the Fraud Hexagon—pressure, opportunity, rationalization, capability, arrogance, and collusion—along with Dark Triad traits (narcissism, Machiavellianism, psychopathy). Data analysis was conducted using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results demonstrate that capability, rationalization, pressure, and collusion significantly influence academic fraud, while opportunity and arrogance do not. Furthermore, Dark Triad personality traits were found to moderate the relationship between arrogance and academic fraud but did not moderate the effects of capability and rationalization. These findings provide theoretical contributions by extending the application of Fraud Hexagon theory within the educational context and integrating personality traits as boundary conditions. Practically, this study implies that universities should strengthen ethical education, digital supervision, and internal control systems while enhancing students’ character and spirituality to mitigate academic dishonesty. Future research should explore each dark personality trait more specifically for nuanced insights.